Analisis Pengelolaan Kearsipan di SMAN 1 Parigi - Fauzan Dhiaulhaq; Ajeng Tanjiah; Jamiludin Jamiludin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This study aims to analyze the management of archives in SMAN 1 Parigi, focusing on the effectiveness of the archival system used and its impact on the efficiency of school administration. The research method used is a case study with a qualitative approach. Data was collected through in-depth interviews with administrative staff, direct observation, and analysis of school archive documents. The results of the study show that archive management at SMAN 1 Parigi still faces various challenges, including the lack of human resources trained in the field of archives, as well as the limitations of supporting infrastructure such as storage space and information technology equipment. Nonetheless, efforts have been made to improve the archival system, such as digitizing some of the archives and increasing the capacity of staff through training. The study also found that better archive management can improve work efficiency and accelerate access to information needed for decision-making. For this reason, it is recommended that schools allocate more resources for the development of the archival system, including increasing staff training, adding storage facilities, and applying more sophisticated information technology. Thus, it is hoped that archive management at SMAN 1 Parigi can run more effectively and support improving the overall quality of school administration.